1995
DOI: 10.1177/000348949510400503
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic and Caldwell-Luc Approaches in Chronic Maxillary Sinusitis: A Comparative Histopathologic Study on Preoperative and Postoperative Mucosal Morphology

Abstract: The aim of the present investigation was to study the histopathologic mucosal changes occurring in chronic maxillary sinusitis both preoperative and postoperative to functional endoscopic sinus (FES) surgery and the Caldwell-Luc (C-L) operation. Correlations were also sought between the histopathologic parameters and endoscopic findings, as well as patient symptoms. Sixty sinuses with the FES surgery and 55 sinuses with the C-L procedure were studied. The histologic parameters were graded semiquantitatively an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 16 publications
0
26
0
3
Order By: Relevance
“…Forsgren et al (15) reported reductions in inflammatory cells and oedema after FESS in a study of 55 operated sinuses. In that study, all nine histological parameters were reduced by a CaldwellÁ/Luc operation but only two of them by FESS.…”
Section: Discussionmentioning
confidence: 97%
“…Forsgren et al (15) reported reductions in inflammatory cells and oedema after FESS in a study of 55 operated sinuses. In that study, all nine histological parameters were reduced by a CaldwellÁ/Luc operation but only two of them by FESS.…”
Section: Discussionmentioning
confidence: 97%
“…In the past, approaches were aggressive, requiring inferior meatal antrostomy and the radical sublabial antrostomy as described by Caldwell and Luc 17,18 . These approaches have been largely replaced by FESS, which allows better diagnostic assessment of the nasal cavities and close monitoring of postoperative progress 19,20 . Nonetheless, FESS can also be conducted at different degrees of invasiveness.…”
Section: Discussionmentioning
confidence: 99%
“…In our Group B, the uncinate process was completely resected. Instead, in Group A we performed a "partial inferior uncinectomy" 3,19,20 . We found that minimally invasive surgery is associated with better clinical outcomes in terms of resolution of pain and optimal functional levels (ventilation), that are identical to those without intervention (controls) and very different than in those submitted to more radical surgeries (Group B).…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory changes were accompanied by oedema and extended to the peribronchiolar tissues [3,21]. It is well accepted that chronic sinusitis is a chronic inflammatory disease of the upper airways, featuring inflammatory cell infiltration, modifications of epithelial differentiation and tissue remodelling, which includes basement membrane thickening, ECM accumulation and oedema [22,23]. These morphological changes are linked to alterations in the activities of both MMP and their counterregulatory inhibitors, TIMP.…”
Section: Discussionmentioning
confidence: 99%